Substance use among Dutch dental students - Plasschaert AJM, Hoogstraten J, van Emmerik BJ, Webster DB, Clayton RR (Blackwell Synergy, 2001)
The objectives were to assess the prevalence of substance use among Dutch dental students and to determine their attitudes about substance use and its consequences. Methods: In association with a national study of drug use among US dental students, a questionnaire was translated from English into Dutch and administered to dental students at two dental schools in The Netherlands.